1984
DOI: 10.1080/03014468400007091
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of the frontal sinus

Abstract: The enlargement of the frontal sinus has been analysed in a longitudinal study of 49 males and 47 females for whom a first lateral cephalogram was available at from 2 to 5 years of age for 88 subjects and from 6 to 11 years for 8 subjects. Thereafter the cephalograms were taken at approximately yearly intervals and in 28 subjects a last cephalogram was taken at 24 years or older. In only six subjects was enlargement of the sinus still proceeding at the time of the last cephalogram . The enlargement was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 3 publications
7
70
0
4
Order By: Relevance
“…However, Brown et al showed that the median age for the first appearance of the frontal sinus was 3.25 years for boys and 4.58 years for girls. 2 The median age at which the main increase in size of the sinus ceased was 15.68 years for boys and 13.72 years for girls. Furthermore, not only the mean skull bone density, but also the bone density of all skull bones separately, displays this phenomenon in our study.…”
Section: Bone Thicknessmentioning
confidence: 99%
“…However, Brown et al showed that the median age for the first appearance of the frontal sinus was 3.25 years for boys and 4.58 years for girls. 2 The median age at which the main increase in size of the sinus ceased was 15.68 years for boys and 13.72 years for girls. Furthermore, not only the mean skull bone density, but also the bone density of all skull bones separately, displays this phenomenon in our study.…”
Section: Bone Thicknessmentioning
confidence: 99%
“…Because the sample of the present study was drawn from the same population as the German study, it may be suggested that internal structures of the skull such as the pneumatic cavities follow distinct growth trajectories. A number of allometric studies on variation in the size of the paranasal sinuses in humans and nonhuman primates [2,17,18,38,39] indicate that the size of the paranasal sinus is a function of body size. However, in view of the finding [10] that the differences in maxillary sinus size between hominoids and macaques cannot be explained simply by differences in skull/body size, it seems reasonable to assume that various factors influence the variation in the morphology of the paranasal sinuses.…”
Section: Growth Of the Maxillary Sinusmentioning
confidence: 99%
“…Moreover, they affirmed that their results regarding frontal sinus size were in agreement with the data from previous X-ray studies. Brown et al 12 found that, upon radiographic examination of the frontal sinus, there was no further expansion after age 15.68 for males and 13.72 for females.…”
Section: Introductionmentioning
confidence: 99%